2019
DOI: 10.3390/ma12203351
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laminin Coating on the Autologous In Vivo Recellularization of Decellularized Vascular Protheses

Abstract: Decellularization of non-autologous biological implants reduces the immune response against foreign tissue. Striving for in vivo repopulation of aortic prostheses with autologous cells, thereby improving the graft biocompatibility, we examined surface coating with laminin in a standardized rat implantation model. Detergent-decellularized aortic grafts from donor rats (n = 37) were coated with laminin and systemically implanted into Wistar rats. Uncoated implants served as controls. Implant re-colonization and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…After decellularization, laminins at the BM of vascular structures were preserved but lost at the place of the odontoblast layer in DPEM (Figure 5C: DPEM), consistent with the published reports (Chen et al, 2015a). Alexa Fluor 488-coupled laminin coating, a continuous, bright green fluorescence, was presented along the surface of laminin-modified DPEM (Figure 5C: DPEM/LN), meaning the method of laminin coating referred to previous reports (Toshmatova et al, 2019) would be feasible to the fabrication of laminin-modified DPEM.…”
Section: Laminin Coating Persistencysupporting
confidence: 89%
See 1 more Smart Citation
“…After decellularization, laminins at the BM of vascular structures were preserved but lost at the place of the odontoblast layer in DPEM (Figure 5C: DPEM), consistent with the published reports (Chen et al, 2015a). Alexa Fluor 488-coupled laminin coating, a continuous, bright green fluorescence, was presented along the surface of laminin-modified DPEM (Figure 5C: DPEM/LN), meaning the method of laminin coating referred to previous reports (Toshmatova et al, 2019) would be feasible to the fabrication of laminin-modified DPEM.…”
Section: Laminin Coating Persistencysupporting
confidence: 89%
“…The fluorescence of laminin still could be detected on the surface of the scaffold even after being seeded and cultured in vitro for 1 week ( Figure 5C ), showing the good persistence of laminin coating. Payam Akhyari et al demonstrated the physical coating of laminin could persist on decellularized grafts for at least 8 weeks in vivo ( Toshmatova et al, 2019 ). Meanwhile, SEM results showed DPSCs presented multilayer growth on the surface of the laminin-coated DPEM ( Figure 5D ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, laminin coating, although of an undefined isoform, has been shown to promote endothelialization while decreasing intimal hyperplasia in aortic grafts in vivo . 6 On the other hand, the α5-containing LN-511 has been shown to be important in the shear stress response of resistance arteries 44 and may be of similar importance in heart valves during the cardiac cycle. The ÎČ-chain is also significant in endothelial BMs as an isoform switch from LN-421 to LN-411 may lead to decreased adhesion and increased endothelial-to-mesenchymal transition.…”
Section: Discussionmentioning
confidence: 99%
“…2 The ideal heart valve replacement is considered to be an offthe-shelf valve that does not exert an immune response and has the capacity to grow and be repopulated by living cells. Therefore, tissue-engineered heart valves, both decellularized and in vitro-produced scaffolds, have been developed and extensively studied in animal models, [3][4][5][6][7][8][9] and decellularized aortic valve allografts have even reached clinical trials. 10,11 Although initial studies have been favorable, tissue-engineered heart valves suffer from structural deterioration similar to conventional allografts and may even be associated with a higher reoperation rate.…”
Section: Introductionmentioning
confidence: 99%
“…(B) Macroscopic appearance and (C) SEM image of decellularized rat aorta. The image is adapted from a report by Sugimura et al ( 56 ) and Toshmatova et al ( 57 ), respectively.…”
Section: Vte Techniquesmentioning
confidence: 99%